A new class of high strength high temperature Cobalt based γ–γ′ Co–Mo–Al alloys stabilized with Ta addition. (15th September 2015) - Makineni, S.K.; Samanta, A.; Rojhirunsakool, T.; Alam, T.; Nithin, B.; Singh, A.K.; Banerjee, R.; Chattopadhyay, K.
Graphical abstract: (left) Plot showing effect of Ta occupancy on formation energy for Co0.75 Al0.125 Mo0.125− x Ta x intermetallic phase in competing DO19 and L12 ordered structures. (middle) Dark field image taken along [0 0 1] zone axis using 100 superlattice L12 ordered spot and (right) APT reconstruction delineated using 10% Al isosurface showing γ′ precipitates (red color) in Co–10Al–5Mo–2Ta heat treated alloy. Abstract: The present paper reports a new class of Co based superalloys that has γ–γ′ microstructure and exhibits much lower density compared to other commercially available Co superalloys including Co–Al–W based alloys. The basic composition is Co–10Al–5Mo (at%) with addition of 2 at% Ta for stabilization of γ′ phase. The γ–γ′ microstructure evolves through solutionising and aging treatment. Using first principles calculations, we observe that Ta plays a crucial role in stabilizing γ′ phase. By addition of Ta in the basic stoichiometric composition Co3 (Al, Mo), the enthalpy of formation (Δ H f ) of L12 structure (γ′ phase) becomes more negative in comparison to DO19 structure. The Δ H f of the L12 structure becomes further more negative by the occupancy of Ni and Ti atoms in the lattice suggesting an increase in the stability of the γ′ precipitates. Among large number of alloys studied experimentally, the paper presents results of detailed investigations on Co–10Al–5Mo–2Ta, Co–30Ni–10Al–5Mo–2Ta and Co–30Ni–10Al–5Mo–2Ta–2Ti. To evaluate the role alloying elements, atom probe tomography investigations were carried out to obtain partition coefficients for the constituent elements. The results show strong partitioning of Ni, Al, Ta and Ti in ordered γ′ precipitates.